IMPROVING STUDENT'S VOCABULARY BY PLAYING PUPPET AT THE THIRD YEAR OF THE ELEMENTARY SCHOOL GABUS 3 SRAGEN IN THE ACADEMIC YEAR 2009/2010 - RAHMAWATI, EMI (2011)
The objectives of the study are to describe: 1) know whether the puppet can improve the students vocabulary or not; 2) the implementation of the using hand puppet to teach English vocabulary of elementary school Gabus 3 Sragen. This research is a classroom action research. The subject of the study is the students of SD Gabus 3 Sragen, especially the third year. This class consists of 15 students as the respondent of research. The object of the study is teaching vocabulary using puppet to third year of SDN Gabus 3 Sragen. The data are collected through test, observation, interview and documentation. The data is done using qualitative analysis. Based on the analysis, the writer draws some conclusions as follows: 1) the implementation student's vocabulary using puppet to the third year of SDN Gabus 3 Sragen was done through puppet, increasing vocabulary, imitating the teacher pronunciation, and evaluating progress; 2) the improvement of teaching vocabulary using puppet to the third year of SDN Gabus 3 Sragen can be seen from the mean score of the pre-test and post-test in each cycle. In the first cycle, the pre-test mean score is 57.00 meanwhile in the second cycle is 61.30. In the first cycle, the post-test mean score is 72.00, meanwhile in the second cycle is 80.00.